Recent HIV infection and annualized HIV incidence rates among sexual and gender minorities in Brazil and Peru (ImPrEP seroincidence study): a cross-sectional, multicenter studyResearch in context - Thiago S. Torres; Sylvia L.M. Teixeira; Brenda Hoagland; Kelika A. Konda; Monica Derrico; Ronaldo I. Moreira; Juan V. Guanira; Marcos Benedetti; Sandro Nazer; Gino M. Calvo; Silver Vargas; Carlos Benites; et al. (Elsevier, 2023)
Summary: Background: HIV incidence estimation is critical for monitoring the HIV epidemic dynamics and the effectiveness of public health prevention interventions. We aimed to identify sexual and gender minorities (SGM) with recent HIV infections, factors associated with recent HIV infection, and to estimate annualised HIV incidence rates. Methods: Cross-sectional multicentre study in HIV testing services in Brazil and Peru (15 cities). Inclusion criteria: 18+ years, SGM assigned male at birth, not using pre-/post-exposure prophylaxis. We identified recent HIV infection using the Maxim HIV-1 LAg-Avidity EIA assay as part of a recent infection testing algorithm (RITA). Annualized HIV incidence was calculated using the UNAIDS/WHO incidence estimator tool. Multivariable logistic regression models were used to estimate factors associated with recent HIV infection. Trial registration: NCT05674682. Findings: From 31-Jan-2021 to 29-May-2022, 6899 individuals participated [Brazil: 4586 (66.5%); Peru: 2313 (33.5%)]; 5946 (86.2%) cisgender men, 751 (10.9%) transgender women and 202 (2.9%) non-binary/gender diverse. Median age was 27 (IQR: 23-34) years. HIV prevalence was 11.4% (N = 784/6899); 137 (2.0%) SGM were identified with recent HIV infection. The overall annualized HIV incidence rate was 3.88% (95% CI: 2.86-4.87); Brazil: 2.62% (95% CI: 1.78-3.43); Peru: 6.69% (95% CI: 4.62-8.69). Participants aged 18-24 years had higher odds of recent HIV infection compared to those aged 30+ years in both countries. Interpretation: Our results highlight the significant burden of HIV epidemic among SGM in large urban centres of Brazil and Peru. Public health policies and interventions to increase access to effective HIV prevention methods such as PrEP are urgently needed in Latin America. Funding: Unitaid, WHO (Switzerland), Ministry of Health from Brazil and Peru.